Production and Marketing Practices in the Florida Nursery Industry, 2008 - Alan Hodges (EDIS)
This 23-page report presents information on production and marketing practices of Florida’s wholesale nursery and greenhouse industry in 2008, with comparisons to the rest of the United States, based on information collected through national mail, Internet, and telephone surveys. Written by Alan Hodges and published by the UF Department of Food and Resource Economics, May 2011.